P‐179: Optics of Curved OLEDs. Issue 1 (29th May 2019) - Cyue, Zih-Rou; Lee, Wei-Kai; Yu, Li-Yu; Su, Guo-Dung; Wu, Chung-Chih
Abstract : Although flexible OLEDs are often used in curved formats and their optics would differ from planar OLEDs, their impacts on OLED emission characteristics are not carefully studied before. Here we investigate optics of curved OLEDs by both optical simulation and experiments and reveal their implications to real flexible OLED applications. We demonstrate light extraction efficiency can be substantially enhanced, or emission profile and viewing angles can be varied, with curved OLEDs in some formats. This may be of use for some special lighting and display applications.